Database Development for Profit Analysis in Book Purchase Transaction Process at Saldira Books Store - Gea, Carlo (Jurnal Sains Indonesia, 2024)
Profit is income derived from business-related transactions, such as the sale of fixed assets, appreciation of asset values ​​and others. In the concept of corporate accounting or finance, profit is net income derived from company activities. Therefore profit and profit analysis is very important. Saldira Books Store performs profit and profit calculation activities manually, so the data obtained is less accurate. Therefore, efforts to calculate profits and profits more accurately are carried out by analyzing each sale made using a database. By using profit and profit analysis on this database, you can find out the amount of profit or profit, what books are most in demand, books that provide the most profit, transactions are clearer, available stocks move more easily and quickly. Database Development using ERC with One To Many type.